漢字の学び方 (Language Circle: Journal of Language and Literature, 2013)
The objectives of teaching kanji characters are among other things that while reading them the learners are able to understand their meaning, to know their forms and how to read them. In speed reading, thorough understanding of such writing system is obligatory. However, the students of Japanese Language Education still face difficulties in understanding such system. What they obtain is merely memorization of the characters; they are unable to read particular characters which are put side by side with other similar characters. Besides, they are also confused when learning the large number of the characters. In order to overcome the difficulties, the writer has provided a correct way of learning how to read such writing system through the following procedures: pay attention to the form of the characters (radical/bushu), pay attention to their sounds (ompu), read the characters, understand their meanings (imi) through learning them at word level (goi reberu). 漢字の学習目標は、読むときに漢字が理解できるようになることで、書くときに漢字が使えることに大別される。読むときに漢字が理解できるためには、漢字の意味を知っていること、漢字の読み方を知っていること、漢字の形が認識できること、漢字語彙の意味がかわり、文を読む際にある程度の遠さで理解することが必要となる。スマラン国立大学の日本語教育プログラムにおいて漢字学習者の場合、初期段階では漢字の形を見分けることが困難なことが多い。そこで、まず、単漢字レベルで漢字の形を提示し、意味、音と対応付けるような活動を行うことが多い。また、漢字を字源やイメージとむすびつけたりストリーを作ったりして意味を記憶するなどの方法もとられる。漢字の学習困難を克服するため、「漢字の形に注目する方法、漢字の読みに注目する方法、漢字の意味に注目する方法、単語レベル方法」の方法を使うのがいいと思う。